Ototoxicity: The Radical Drum Beat and Rhythm of Cochlear Hair Cell Life and Death. (May 2018) - Gauvin, David V.; Yoder, Joshua; Zimmermann, Zachary J.; Tapp, Rachel
The function and structure of the auditory information processing system establishes a unique sensory environment for the "perfect storm." The battle between life and death pits the cascade of an apoptotic storm, programmed cell death cascades, against simple cell death (necrosis) pathways. Live or die, the free radical biology of oxygen and hydroxylation, and the destruction of transition metal migration through the mechanical gate sensory processes of the hair cell lead to direct access to the cytoplasm, cytoplasmic reticulum, and mitochondria of the inner workings of the hair cells. These lead to subsequent interactions with nuclear DNA resulting in permanent hearing loss. The yin and yang of pharmaceutical product development is to document what kills, why it kills, and how do we mitigate it. This review highlights the processes of cell death within the cochlea.